The TRAIL in the Treatment of Human Cancer: An Update on Clinical Trials - Snajdauf, Martin; Havlova, Klara; Vachtenheim, Jiri; Ozaniak, Andrej; Lischke, Robert; Bartunkova, Jirina; Smrz, Daniel; Strizova, Zuzana (Frontiers in Molecular Biosciences, 2021)
TRAIL (tumor-necrosis factor related apoptosis-inducing ligand, CD253) and its death receptors TRAIL-R1 and TRAIL-R2 selectively trigger the apoptotic cell death in tumor cells. For that reason, TRAIL has been extensively studied as a target of cancer therapy. In spite of the promising preclinical observations, the TRAIL-based therapies in humans have certain limitations. The two main therapeutic approaches are based on either an administration of TRAIL-receptor (TRAIL-R) agonists or a recombinant TRAIL. These approaches, however, seem to elicit a limited therapeutic efficacy, and only a few drugs have entered the phase II clinical trials. To deliver TRAIL-based therapies with higher anti-tumor potential several novel TRAIL-derivates and modifications have been designed. These novel drugs are, however, mostly preclinical, and many problems continue to be unraveled. We have reviewed the current status of all TRAIL-based monotherapies and combination therapies that have reached phase II and phase III clinical trials in humans. We have also aimed to introduce all novel approaches of TRAIL utilization in cancer treatment and discussed the most promising drugs which are likely to enter clinical trials in humans. To date, different strategies were introduced in order to activate anti-tumor immune responses with the aim of achieving the highest efficacy and minimal toxicity. In this review, we discuss the most promising TRAIL-based clinical trials and their therapeutic strategies.